1989
DOI: 10.1002/jcp.1041380104
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cyclic AMP synthesis by forskolin is followed by a reduction in the expression of c‐myc messenger RNA and inhibition of 3H‐thymidine incorporation in human fibroblasts

Abstract: We have studied the effect of increased intracellular levels of cyclic AMP on the growth response to platelet-derived growth factor (PDGF) of human foreskin fibroblasts in culture. It was found that forskolin, a potent stimulator of adenylate cyclase activity, inhibits the stimulatory effect of PDGF on 3H-thymidine incorporation with a dose dependence similar to that observed with regard to cyclic AMP formation. A time-course study indicated that forskolin has no effect on ongoing DNA synthesis but affects eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 37 publications
(31 reference statements)
2
37
1
Order By: Relevance
“…It is interesting to note that in contrast to the results presented here, increased cAMP has been shown to down-regulate c-myc mRNA expression in several cell types, including normal and neoplastic B cells (19), leukemic cells (20), fibroblasts (21), and a macrophage cell line (22). The cAMP-mediated reduction in c-myc RNA levels results from a decrease in c-myc transcription (20,22).…”
Section: Discussioncontrasting
confidence: 79%
“…It is interesting to note that in contrast to the results presented here, increased cAMP has been shown to down-regulate c-myc mRNA expression in several cell types, including normal and neoplastic B cells (19), leukemic cells (20), fibroblasts (21), and a macrophage cell line (22). The cAMP-mediated reduction in c-myc RNA levels results from a decrease in c-myc transcription (20,22).…”
Section: Discussioncontrasting
confidence: 79%
“…In this study we found that activation of both kinases A and C (by forskolin and TPA respectively) inhibited the relocalization of /3-actin mRNA in serum-stimulated cells and caused delocalization of mRNA in cells grown in normal growth conditions. The inhibitory effect of these kinases on other PDGFinduced events is downstream of the receptor tyrosine kinase (Heldin et al, 1989;Graves et al, 1993), however beyond this the targets are not known. Activation of ras by PDGF is effected through several intermediate proteins (Lowenstein et al, 1992;Li et al, 1994;Chardin et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…. ; Heldin et al, 1989;Mechta et al, 1989;Cowlen and Eling, 1992), repression of D-type cyclins (cyclin D1, cyclin D3; Cocks et al, 1992;Sewing et al, 1993;Ward et al, 1996;L'Allemain et al, 1997), and accumulation of the p27 kip1 CDK inhibitor Ward et al, 1996;van Oirschot et al, 2001;Kuiperij et al, 2005), which inhibits both CDK4 and CDK2 Kuiperij et al, 2005) and thus inactivating phosphorylations of pRb. Inhibition of cyclin D1-CDK4 activity by cAMP-dependent accumulation of p27 has been ascribed to p27 impairing the activating T172-phosphorylation of CDK4 by the constitutively active CDK-activating kinase (CAK, cyclin H-CDK7-Mat1; Kato et al, 1994).…”
Section: Introductionmentioning
confidence: 99%